Records on the Road Stop in Dilunto - Samadžić, Gligor (Collection of Papers of the Faculty of Philosophy in Priština, 2020)
The paper presents data on the location of the road stop in Dilunto, which was the part of the Narona (Vid near Metkovići) – Ad Zizo (Mosko/Ukšić) Roman road, today’s Stolac. The remains of ancient settlements, smaller buildings used for various economy-related purposes, stairs, fortifications with wide walls, the remains of city square, public buildings, and a cistern were found on the a forementioned road in Stolac (Zagrađe, Podgrađe, Njivice, Carine,Bačve-Kućište, Čairi, Veliki Svrdo). A huge number of smaller, movable remains, especially, ceramic, iron, bronze, glass, and silvero bjects, as well as different moulds, money, jewellery, and tools, were found together with immovable objects. Ancient Dilunto is located in the period between 1st and 4th century according to the oral and epigraph sources as well as archaeological materials (the remains of buildings, money, ceramics, bricks).
Keywords: the road stop in Dilunto; the Nrona–Ad Zizio road; Doarsi; Stolac; East Herzegovina